MENINJAU SUSTAINABLE COMPETITIVE ADVANTAGE: PERAN ENTREPRENEURIAL ORIENTATION, KNOWLEDGE MANAGEMENT, DAN MARKETING INNOVATION - Elidawaty Purba; Yeni Ariesa; Liharman Saragih; Darwin Damanik; Acai Sudirman (AdBispreneur : Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2022)
The primary purpose of this study is to determine the contribution of entrepreneurial orientation, knowledge management and marketing innovation in influencing sustainable competitive advantage.The sample in this study amounted to 100 respondents who were none other than business owners which were then determined by a convenience sampling approach. Data collection uses a questionnaire instrument which is then distributed online. Data analysis using SPSS application through multiple regression analysis test, coefficient of determination and hypothesis testing. Based on the results of data analysis, conclusions are obtained entrepreneurial orientation contributes positively and significantly to sustainable competitive advantage. Subsequent research results confirm knowledge management contributes positively and significantly to sustainable competitive advantage. The results of the latest research explain that marketing innovation contributes positively and significantly to sustainable competitive advantage.Tujuan utama penelitian ini untuk mengetahui kontribusi entrepreneurial orientation, knowledge management, dan marketing innovation dalam mempengaruhi sustainable competitive advantage. Sampel dalam penelitian ini berjumlah 100 responden yang tidak lain adalah pemilik usaha yang selanjutnya ditentukan dengan pendekatan convenience sampling. Pengumpulan data menggunakan instrumen kuesioner yang kemudian dibagikan secara online. Analisis data menggunakan aplikasi SPSS melalui uji analisis regresi berganda, koefisien determinasi dan uji hipotesis. Berdasarkan hasil analisis data, diperoleh kesimpulan entrepreneurial orientation berkontribusi positif dan signifikan terhadap sustainable competitive advantage. Hasil penelitian selanjutnya mengkonfirmasi knowledge management berkontribusi positif dan signifikan terhadap terhadap sustainable competitive advantage. Hasil penelitian terakhir menerangkan bahwa marketing innovation berkontribusi positif dan signifikan terhadap sustainable competitive advantage.